Bringing Time into Molecular and Cellular Biology (Journal of Analytical Oncology, 2013)
In conjunction with the defense of a doctoral thesis on the deciphering of complex protein interactions on living cells, six scientists shared their view on time in molecular and cellular biology. This brief review takes the form of a conference report and summarizes the contributions of the speakers and the defense. Opportunities and challenges for time resolved assays in molecular and cellular biology were vividly discussed during two days with a pan-European audience. Awareness of biological timeframes and understanding the temporal aspects were claimed critical for analytical applications in biology.